The lingam inside the garbhagriha of Jabreshwar Mahadev temple - Ghosh, Ayan (2023)
Jabreshwar Mahadev Temple is managed by the Mangaldas Trust and maintained by the priest family who live within the temple premise. The temple is dedicated to Lord Shiva. A stone lingam is worshipped in the garbagriha along with the goddess Parvati. Nandi and Hanuman are worshipped in the sabhamandap. All temples at Walkeshwar remain closed from 1pm to 4pm when the garbagriha is cleaned and the dieties washed.